The Impact of Cruise Ship Passengers in Maine: The Example of Bar Harbor - Gabe, Todd; Lynch, Colleen; McConnon, James (Maine Policy Review, 2003)
Maine’s expanding cruise ship industry can provide local economic benefits and add to the state’s already large tourism economy. The authors describe results of a survey they conducted among passengers from eight ship visits to Bar Harbor, a town that has emerged as a popular port of call on New England summer and autumn cruises. They found that cruise ship passengers have higher household incomes and spend substantially more per day than typical Maine tourists. They make several suggestions for how ports can maximize the benefits from cruise ship passengers. These include using cruise ship visits to extend the local tourism season; converting “non-spending” passengers to “spenders;” implementing strategies to encourage and track return visits by passengers; and developing management plans to direct the flow of passengers through town.